Immobilized Plant-Based Presumptive Probiotics as Functional Ingredients for Breakfast Cereals - Chrysoula Pavlatou; Ioanna Prapa; Electra Stylianopoulou; Gregoria Mitropoulou; George Skavdis; Yiannis Kourkoutas (Fermentation, 2025)
Seven wild-type lactic acid bacteria, belonging to Lactiplantibacillus plantarum and Lactococcus cremoris species, were isolated from beetroots and white mushrooms and evaluated for their safety and functional profile. Lc. cremoris isolates were sensitive to all antibiotics tested, while L. plantarum strains exhibited resistance in certain antibiotics. Among them, Lc. cremoris FBMS_5810 showed the highest cholesterol removal ability (51.89%) and adhesion capacity to Caco-2 cell lines (32.14%), while all plant origin strains exhibited strong antagonistic and inhibitory activity against foodborne pathogens, as well as high survival potential during an in vitro digestion model. Subsequently, freeze-dried immobilized Lc. cremoris FBMS_5810 cells on oat flakes were prepared with initial cell loads >8.5 log CFU/g, and the effect of trehalose as a cryoprotectant in cell viability during storage at room and refrigerated temperatures for up to 180 days was studied. A significant reduction in cell loads was observed in all cases studied. However, freeze-dried immobilized Lc. cremoris FBMS_5810 cells on oat flakes prepared using trehalose as a cryoprotectant stored at 4 °C exhibited the highest cell viability (8.75 log CFU/g) after 180 days. In the next step, functional breakfast cereals enriched with freeze-dried immobilized Lc. cremoris FBMS_5810 cells on oat flakes (produced with (MLT) or without (ML) trehalose) were developed and stored at room and refrigerated temperatures for 180 days. The initial cell levels ≥ 9.18 log CFU/g were achieved, while a significant decrease was recorded during storage in all cases. The maintenance of cell loads ≥ 7.75 log CFU/g was documented in the case of both ML and MLT samples stored at 4 °C; however, the presence of trehalose in MLT samples resulted in cell viability 7.52 log CFU/g after 180 days of storage at room temperature. Importantly, the functional breakfast cereals were accepted by the panel during the sensory evaluation.